Reading Through Emotions: An Affective Narratolological Approach to Alice Munro's Short Stories - Sahar Sadeghi; Hossein Pirnajmuddin; Zahra Jannessari Ladani (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2021)
The emergence of fields of study like emotionology, affective narratology, and psychonarratology in recent decades evidences a dramatic rise in research done on the meaning and interpretation of emotions. Affective Narratology as one of the recent fields in emotion studies attempts to identify and account for the figuration of emotions in works of literature. Focusing on three basic emotions (shame, jealousy and love) figuring in Alice Munro’s selected short stories this paper probes the significance of emotional registers in the writer's depiction of daily life. Examined is the way the stories' sincere tone and their comprehensible, ordinary language, contribute to the emotional identification of readers with characters. Applying affective narratological theories, the objective is to show how emotions contribute to plot development and characterization in these stories. Central to the analysis is interpreting emotional moments experienced by characters, especially female characters